Factors influencing parents' involvement in guiding their children's studies in kindergarten in Penang / Jaya Kumar Shanmugam ... [et al.] - Shanmugam, Jaya Kumar; Kalimuthu, Kalaivani; Pranee, Lai; Yin, Chung Jiun
Parental involvement is one of the most important roles for helping children achieving greater academic success. This study investigated the factors influencing parents' involvement towards guiding their kindergarten children's studies in Penang. Parental involvement was depicted as the dependent variable whereas parents' expectation, parents' self-efficacy, communication barrier and household wealth as the independent variables. Correlational quantitative design method was used in the research study. Data was collected using questionnaires and the targeted population was 100 parents whose children were studying in any kindergarten in Penang but only 59 participants responded. The findings showed that there was significant positive relationship between parental involvement and parents' expectation, parents' self-efficacy, communication barrier and household wealth.